A DEVELOPMENT OF SOCIAL RESPONSIBILITY INDICATORS ON ETHICAL RESPONSIBILITIES OF UNDERGRADUATE STUDENTS IN KING MONGKUT’S INSTITUTE OF TECHNOLOGY - พลรักษ์, มณฑา; ทรงบัณฑิตย์, อภิธีร์; บูรศิริรักษ์, สมบูรณ์; มาลารัตน์, อนันต์ (Journal of Industrial Education, 2016)
The purposes of the research were to study the development of social responsibility indicators on ethical responsibilities of undergraduate students in King Mongkut’s Institute of Technology and then to test the consistency of the measurement model on social responsibility indicators. The research procedures were divided into 2 steps. Step 1 : Setting the development of indicators on ethical responsibilities by studying, analyzing, synthesizing the related literatures and in-depth interviewing 17 experts. Step 2 : Testing the consistency of the measurement model on social responsibility indicators by using the questionnaire to collect data from undergraduate students at the number of 1,500. Data were analyzed by using the statistics as mean, standard deviation, and coefficient of correlation by statistical package and confirmatory factor analysis by LISREL program. The research results were as follows: The indicators of social responsibility on ethical responsibilities of undergraduate students in King Mongkut’s Institute of Technology consisted to 4 views :1) benefit view consisted with 40 indicators, 2) individual view consisted with 35 indicators, 3) moral view consisted with 37 indicators and 4) fairly view consisted with 38 indicators. The measurement model on social responsibility indicators of undergraduate student in King Mongkut’s Institute of Technology was related to the empirical data at .05 significantly.